Sighting heterogeneity of right whales in the western North Atlantic: 1980-1992 - Brown, Moira W.; Brault, Solange; Hamilton, Philip K.; Kenney, Robert D.; Knowlton, Amy R.; K. Marx, Marilyn; A. Mayo, Charles; Slay, Christopher K.; Kraus, Scott D. (J. Cetacean Res. Manage., 2020)
The population of western North Atlantic right whales (Eubalaena glacialis) is distributed primarily between Florida, USA and Nova Scotia, Canada, aggregating seasonally in five geographically distinct, high-use areas. To test the effectiveness of monitoring all demographic classes (juvenile and adult males and females) of the population in these five habitat areas, an evaluation was carried out of the identification records of catalogued right whales collected between 1980 and 1992, for which the age, sex and reproductive status (for adult females) were known. The mean annual identification frequency of adult females was significantly lower than that of adult males, juvenile females and juvenile males. Among adult females, reproductively active females were seen significantly more often than expected when lactating (with a calf) than during their pregnancy or resting years. These data suggest that, while research efforts in the five high-use habitat areas have had relatively equal success at monitoring juvenile males and females and adult males, many adult females are segregated at times from the rest of the population. Lower variability in annual identification frequencies of adult females indicates that they may be more site specific in their distribution than males, particularly during the years when they are pregnant or resting from a previous pregnancy. Re-running these analyses using sighting records updated through 2000 will help determine if the trends continue to be documented regardless of changes in survey effort and patterns of habitat use of some animals.